2018
DOI: 10.1016/j.intimp.2018.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Mimetic peptide AC2-26 of annexin A1 as a potential therapeutic agent to treat COPD

Abstract: Chronic obstructive pulmonary disease (COPD) is related to inflammatory process caused by smoking habit. In this scenario, the anti-inflammatory protein Annexin A1 (AnxA1) may represent a therapeutic alternative. We performed experiments to evaluate the effects of the AnxA1 mimetic peptide Ac2-26 in an initial COPD model by physiological, histopathological, biochemical and immunohistochemical analyses. Weight loss, increased blood pressure, reductions in the pulmonary frequency and ventilation, loss of trachea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Experiments have confirmed that ANX‐A1 inhibits the adhesion of PMNs to endothelial cells by inducing L‐selectin detachment in neutrophils and simultaneously activates caspase‐3 to promote PMN apoptosis to regulate inflammation 32 . In a smoke‐induced rat lung inflammation model, the use of Ac2‐26 alleviated lung epithelial damage caused by smoke exposure 33 . In the IR‐induced ALI model, the use of Ac2‐26 significantly reduced lung neutrophil infiltration, improved lung injury scores and provided lung protection 34 .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Experiments have confirmed that ANX‐A1 inhibits the adhesion of PMNs to endothelial cells by inducing L‐selectin detachment in neutrophils and simultaneously activates caspase‐3 to promote PMN apoptosis to regulate inflammation 32 . In a smoke‐induced rat lung inflammation model, the use of Ac2‐26 alleviated lung epithelial damage caused by smoke exposure 33 . In the IR‐induced ALI model, the use of Ac2‐26 significantly reduced lung neutrophil infiltration, improved lung injury scores and provided lung protection 34 .…”
Section: Discussionmentioning
confidence: 93%
“…There was no significant difference between the two groups. The reason may be that (a) the inflammation caused by lung IR was inhibited after adding Ac2‐26 33 ; (b) in the COPD model, 35 Lucas et al proposed that the reduction in endogenous ANX‐A1 after Ac2‐26 injection was associated with negative feedback regulation. (c) There are also studies 36 indicating that Ac2‐26 may regulate the conversion of endogenous ANX‐A1 between 37 and 34 kDa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Annexin A1 and its derivative peptides have been shown to have therapeutic effect in various disease states, including sepsis ( Gavins et al, 2012 ; Zhang et al, 2018 ), lung inflammation ( da Cunha et al, 2012 ) and chronic obstructive pulmonary disease (COPD) ( Possebon et al, 2018 ), myocardial infarction ( D’ Amico et al, 2000 ; La et al, 2001 ; Qin et al, 2015 ), and intestinal wound repair ( Babbin et al, 2008 ). Studies confirmed that endogenous annexin A1 plays a role in promoting phagocytosis ( Yona et al, 2006 ; Scannell et al, 2007 ), and its derived peptide Ac2-26 increases macrophage phagocytosis of apoptotic polymorphonuclear leukocytes (PMNs) ( Maderna et al, 2005 ).…”
Section: Therapeutic Applications Of Annexins and Analogue Moleculesmentioning
confidence: 99%
“…Studies confirmed that endogenous annexin A1 plays a role in promoting phagocytosis ( Yona et al, 2006 ; Scannell et al, 2007 ), and its derived peptide Ac2-26 increases macrophage phagocytosis of apoptotic polymorphonuclear leukocytes (PMNs) ( Maderna et al, 2005 ). Ac2-26 administration in murine lipopolysaccharide (LPS) models of sepsis has demonstrated inhibition of cardiomyocyte apoptosis and myocardial damage ( Zhang et al, 2018 ), reduced leukocyte adhesion and cerebrovascular inflammatory response in the brain ( Gavins et al, 2012 ), and reduced inflammatory cytokine release and subsequent decreased inflammation in lung ( da Cunha et al, 2012 ; Possebon et al, 2018 ). Another annexin A1 analogue (CR-Ac 2-50 ) reduces inflammation and attenuates myocardial dysfunction in a polymicrobial sepsis model ( Dalli et al, 2013 ; Gobbetti et al, 2014 ).…”
Section: Therapeutic Applications Of Annexins and Analogue Moleculesmentioning
confidence: 99%